A Deeper Understanding of Income Tax Article 21: Definition, Subjects, and Objects - Cut Yusniar Eka Putri; Galuh Tresna Murti; Sicilya Khairunnisa; Achmad Kurniawan Syabana (Jurnal Riset Perpajakan: Amnesty, 2023)
This article discusses Article 21 of Income Tax (PPh 21) imposed on income such as salaries, wages, honorarium, and benefits received by individuals or entities in a tax year. This study aims to understand PPh 21 by analyzing the definition, deduction, subject, object, and final income. The method is a literature review that extracts information from various sources. PPh 21 is a withholding tax on domestic individual income from work, services, or activities. The deductor can be an individual or a permanent business entity that is obliged to withhold taxes. Tax subjects are those who pay income tax 21, while non-subjects include entities such as representative offices of foreign countries. Tax objects are income that is subject to tax, such as salary, pension, or honorarium, while non-tax objects are income that is not subject to taxation. PPh 21 is final on income such as severance pay from pension funds authorized by the Minister of Finance, pension benefits, old-age benefits, and honorarium. This article supports a better understanding of PPh 21 and its important role in state revenue. Taxes are a key aspect in the development of the country, and a solid understanding of the tax system, subjects, and objects of taxes is essential to support the interests of the people and the progress of the country.